Effects of initial planting method on the performance of mixed plantings of alder and oak on compacted opencast coal-spoils, Wales: 10-year results. Issue 4 (19th May 2017) - Plamping, K.; Haigh, M.; Reed, H.; Woodruffe, P.; Fitzpatrick, S.; Farrugia, F.; D'Aucourt, M.; Flege, A.; Sawyer, S.; Panhuis, W.; Wilding, G.; Cullis, M.; et al.
Abstract: The degradation of formerly reclaimed opencast coal-land is a problem for Wales. This project explores strategies for community-based volunteers aiming to re-establish self-sustaining woodland. It evaluates three planting methods (forestry-style notch-planting, parks-and-gardens-style pit-planting and orchard terrace-style trench-planting) through a 10-year formal experimental trial using common alder and oak. Ten year survival for alder was (39%) and oak (79%). More trench-planted trees survived than pit-planted or notch-planted. Ten-year growth of trench-planted alder and oak also exceeded that of pit-planted and notch-planted. Earthworm biomass was greater under alder than grass; earthworm biomass in trench-planted and pit-planted areas was >3.5 times more than notch-planted areas.